Locations and Relocations: Modelling, Determinants, and Interrelations - Miguel C. Manjon-Antolin; Josep Maria Arauzo-Carod (European Regional Science Association (ERSA), 2006)
This paper analyses the determinants of industrial location processes distinguishing between the location of new establishments and the relocation of extant establishments. Using data from the Catalan Industrial Establishments Register covering 946 municipalities over the period 2001-2004 we find that institutional characteristics, such as e.g. being capital of the province, strongly affect the location decisions of industrial establishments. In contrast, measures of agglomeration and location economies are not that important. We also find a close statistical relation between new locations and relocations. We discuss several econometric strategies based upon Poisson models for cross-section and panel data, thus providing alternative sets of estimates to address the robustness of our conclusions.
Keywords: 330